PENDIDIKAN AGAMA DALAM KULTUR SEKOLAH DEMOKRATIS: POTENSI MEMBUMIKAN DERADIKALISASI AGAMA DI SEKOLAH - Herly Jannet (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
This study aimed in general to determine and describe the religious education in a democratic school culture is one of potential strategies in disseminating religious de-radicalization in schools. Applying qualitative naturalistic approach with case study, this study focused the location in Christian High School Urimessing Ambon. The object of this research was the all democratic phenomena found in the process of teaching and learning of Christian education. The results of this study can be described as follows: religious education in a democratic school culture has the potential to disseminate de-radicalization because the learning process optimized the attitude of critical thinking on freedom, independence, and accountability that were assumed to build the belief, attitude and norm of student to: (1) deepen and believe their own religious teachings; (2) commit to transform their religious teacgings in their daily life, both individually and socially; and (3) become the real who got off from violence and anarchy in realizing their objectives.